VARIAN NON-DELESI 9 PASANG BASA DNA MITOKONDRIA MANUSIA SAMPEL FORENSIK BALI - Gumilar, Gun Gun; Noer, A. Saifuddin (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2005)
One of human mitochondrial DNA (mtDNA) variant is a 9 base pairs (bp) deletion in the COII/tRNALys intergenic region. In construction mtDNA nomenclature, 9-bp deletion database consist of primary and secondary data is needed, including Bali bombing forensic samples. Here we report a 9-bp non- deletion mtDNA variant from Bali bombing forensic samples to complete primary data. Polymerase Chain Reaction (PCR) technique with 2 set primer was used to detect 9-bp deletion. The PCR result was detected by agarose gel electrophoresis, which showed two bands (0.1 and 0.4 kb) for non-deletion variant control, and one band (0.4 kb) for deletion variant control. If the sample has 9-bp deletion, only one of the primer pairs could amplify a fragment of 0.4 kb. If the sample does not have 9-bp deletion, the other primer pair will amplify a 0.1 kb product. The result showed that none of the 24 samples has 9-bp deletion. These results are contributed to the human mtDNA database and nomenclature construction. Keywords: mtDNA, 9-bp deletion, PCR